The Economic Thought of Jonathan Edwards - Valeri, Mark (Church history, 1991)
On 16 March 1742, Jonathan Edwards's church in Northampton adopted a new covenant of faith. Written in the heat of the Great Awakening, the document began, predictably, by acknowledging “the blessed manifestations and fruits of [God's] gracious presence in this town” during the recent spiritual revivals. It then plunged into more worldly matters. It called on every church member to deal honestly and justly in secular business: they were not “in any matter” to “overreach or defraud” their “neighbor…and either willfully or through want of care, injure him in any of his honest possessions or rights.” The oath became more explicit. Debtors were to pay their creditors, so to avoid “willfully or negligently” wronging others. Indeed, debtors promised to forego “rest till … that restitution, or …that satisfaction” were effected. Likewise, creditors pledged to eschew “wordly gain, or honor, or interest…or getting the better” of their “competitors” as the “governing aim” of their business. Those who managed public affairs also were to forsake competitiveness. They agreed to relinquish their private interests for the sake of equity, especially “concerning any outward possessions, privileges, rights or properties.” Although the covenant dealt with other matters, it sustained its striking focus on commerce. Even as it neared its conclusion, it used economic metaphor to urge piety, presenting life as capital “to be laboriously spent in the business of religion: ever making it our greatest business.”